Opioid Consumption and Time to Return to Work After Percutaneous Foot and Ankle Surgery - Jimmy J. Chan MD; Javier Z. Guzman MD; Kevin K. Chen; Jesse C. Chan; Ettore Vulcano MD (Foot & Ankle Orthopaedics, 2019)
Category: Hindfoot, Lesser Toes, Midfoot/Forefoot Introduction/Purpose: Orthopaedic surgeons are the 5th highest prescriber for narcotics in the USA. Foot and ankle procedures can be amongst some of the more painful procedures in orthopedics. A recent study demonstrated that patient underwent open foot and ankle surgeries averaged 27.2 tablets of narcotics with 37% of patients unwilling to stop at 3-month post-operative visit. Percutaneous techniques for foot and ankle procedures were recently approved in the U.S., which allow for significantly smaller incisions and minimal soft tissue disruption, which may potentially decrease post-operative pain and allow faster recovery. The purpose of this study is to assess the total opioid consumption and time for return to work following percutaneous foot and ankle surgery. Methods: In this prospective cohort study, 50 consecutive patients underwent percutaneous foot surgery (bony procedures with or without soft tissue work) by a single surgeon. All surgeries were outpatient procedures and performed under general anesthesia with a long-acting popliteal nerve block. All patients were prescribed 30 tablets of 5 mg oxycodone, 50 tablets of 500 mg acetaminophen, and 9 tablets of 600 mg ibuprofen post-operatively for pain control. All patients were given a log sheet to record number of pain medications taken during the first 14 post-operative days. The log sheet and leftover pills were collected and counted to confirm the amount of pain medication used at 2-week post-operative visit. Time return to work was also recorded in subsequent follow-up appointment. Results: All 50 patients returned their log sheet at 2-week post-operative visit. Mean age was 47.1 years. N=36 (72%) were forefoot surgeries, N=2 (4%) midfoot, N=9 (18%) hindfoot, and N=3 (6%) combined. Average oxycodone tablets taken during the first 14 days after surgery was 3.3 tablets. By the 14th day, no patient was taking any narcotic medication. The average return to work was 18.9 days post-operatively. Patients with forefoot surgery averaged 2.2 tablets of oxycodone with return to work at 10.4 days. Midfoot surgery patients averaged 3.5 tablets with return to work at 33 days. Hindfoot surgery patients averaged 5.3 tablets with return to work at 38.9 days. Combined foot surgery patients averaged 11 tablets with return to work at 54.3 days. Conclusion: This study demonstrated that percutaneous foot and ankle surgery has significant reduction and cessation in narcotic consumption post-operatively when compared to the reported values with open procedures in current literature.